Development of biomechanical behaviour of magnesium alloys for biomedical context - Hamza Abu Owida; Feras Alnaimat; Bassam Al-Naami; Jamal Al-Nabulsi; Nidal Turab (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Magnesium alloys, which belong to the category of biodegradable metals, have a significant amount of potential to be utilized as implant materials, and as a result, they draw a lot of attention. This article is a review that summarizes the mechanical properties of magnesium alloys that are used in medical applications. This article illustrates the mechanical behaviors of magnesium alloys that are used in biomedical applications as well as the ways that may be used to improve the mechanical characteristics of biodegradable magnesium alloys. In conclusion, the difficulties that will need to be overcome in the creation of biodegradable magnesium alloys are discussed.